Estimates of the Impact of Crime Risk on Property Values from Megan's Laws - Linden, Leigh; Rockoff, Jonah E (American Economic Review, 2008)
We estimate the willingness to pay for reductions in crime risk using the location and move-in dates of sex offenders. We find significant effects of sex offenders' locations that are geographically localized. House prices within 0.1 miles of a sex offender fall by 4 percent on average. We then use this finding to estimate the costs to victims of sexual offenses, and find costs of over $1 million per victim—far greater than previous estimates. However, we cannot reject the alternative hypotheses that individuals overestimate risks posed by offenders or that living near an offender poses significant costs exclusive of crime risk. (JEL K42, R23, R31)